The Narration of Symbolic Animalistic Metaphors in Indonesian Contemporary Painting - Vina Meilinda (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
This research aims to describe the symbolic narrative of animalistic metaphors in Indonesian contemporary painting as a medium of criticism of the socio-political dynamics in Indonesia. The method used in this research is qualitative with Paul Recouer's Hermeneutic approach that interprets animalistic symbols through layers of literal meaning. The data in the research shows the meaning of the animalistic metaphor in painting that presents visual symbols resulting from the creative expression of artists, including Djoko Pekik, Gatot Indrajati, and Suraji. The animalistic metaphor in Indonesian contemporary painting is one of the symbolic aspects of the similarity of human nature or political rulers with the nature of animals that are considered to have savage, wild, greedy and have no conscience. Each artist has his own way of delivering criticism through painting by using historical dramatization, humor, and satire. The animalistic metaphors in these works are coupled with the selection of titles that lead to a parody. The animalistic metaphor is told visually narrative, expressing the artist's expression of anxiety and criticism that is able to bridge the aesthetic experience and critical reflection on the reality of Indonesia's current socio-political condition.